Financialisation and the portuguese private consumption: two contradictory effects? - Gonçalves, A.; Barradas, R. (Dinâmia’CET-IUL Working Paper Nº 2018/02, 2018)
This paper makes an empirical evaluation of the relationship between financialisation and the Portuguese private consumption by performing a time series econometric analysis from the first quarter of 1996 to the last quarter of 2016. Framed within the post-Keynesian literature, financialisation has two contradictory effects on private consumption. The first one corresponds to the fall in the households’ labour income, which favours a deceleration of private consumption. The second one corresponds to the increase of households’ financial and housing wealth, which favours an acceleration of private consumption. The global net effect of financialisation tends to be positive because the beneficial wealth effect suppresses the harmful income effect. We estimated a private consumption equation that includes four control variables (unemployment rate, inflation rate, short-term interest rate and long-term interest rate) and three variables linked to financialisation (labour income, financial wealth and housing wealth). Our results confirm that labour income, financial wealth and housing wealth are positive determinants of Portuguese private consumption. Our results also show that financialisation has represented an important driver of Portuguese private consumption, particularly due to the beneficial effects of financial wealth.